Mobile app for audience engagement - Goh, Chong Rui (2019)
In events, audience interaction and engagement are very important factors as they directly depict whether the event is a success. As such many methods have been derived to increase audience participation, such as games, quiz and physical feedback segment, where audience will fill up a form stating how satisfied are, they with the events. As we move on to the digital era, internet and mobile devices are becoming an integral part of our lives. An organisation that does not leverage on technology will lose out on a huge market share. Hence, there are multiple applications and website developed just for event moderators to help capture audience attention. However, these technologies mostly apply to formal events like training or seminars. There is a lack of audience interaction application for informal events like wedding dinners or school orientation camp. Therefore, this project is developed to fulfil the task of providing fun and interactives to audience in an informal setting. This project is created as an electronic lottery system where audience can partake in the lottery and win prizes. It is developed with as a web based mobile application, developed with HTML5, Javascript as the front end development and Visual studio ASP.NET as backend development language. This report will detail the main procedures on participating in the lottery system and the research and the further improvements that can be implemented to this project to make it more interactive. In conclusion, this application managed to fulfil the crucial project objectives to be used as an interactive platform for informal events.